Perdebatan Zakat Dalam Ekonomi Islam: Menilai Zakat Profesi Dari Perspektif Ulama Kontemporer - Musanna, Khadijatul; Makraja, Fahmi; Yanti, Fitri (Universitas Muhammadiyah Surabaya, 2024)
Abstract: Professional zakat or income zakat is zakat that must be paid because it has reached the nisab of assets and is perfect haul based on income obtained from a particular business or work, whether carried out personally or by institutions, organizations and groups. This study aims to determine the literature of muamalah scholars related to professional zakat. This study uses qualitative research methods by examining data based on literature from books and books about professional zakat. The results of the research in this study can be conveyed by the author that in the Fiqh Muamalah literature each ulema has his own perception regarding the implementation of professional zakat. It can be clearly seen that there is an error in the provisions of assets subject to professional zakat, such as the opinion of Yusuf Al-Qardhawi requiring professional zakat every monthly salary as a farmer who pays zakat every harvest, provided that it has reached the nisab. Meanwhile, according to the opinion of Shaykh Bin Baz and Shaykh Muhammad bin Saleh Al Utsaimin, it is not obligatory for a professional zakat to be paid for someone who, after receiving his salary, is used to fulfill his daily needs so that there is no salary left in the following month, but zakat may be imposed if each time If the salaryman sets aside part of his income as savings, then it is obligatory for him to issue zakat with the provisions of perfect haul and property. In the opinion of the writer, professional zakat tends to be as conveyed by Yusuf Al-Qardhawi. According to the author of Shaykh Muhammad's opinion, if the consideration is to meet daily needs, humans will never have enough with all types of needs, so they always feel inadequate and in the end don’t pay zakat. Keywords: Fiqh Muamalah, Professional Zakat, Islamic Law.